A prospective, randomized, Single-blinded, comparative study of Classic Laryngeal Mask Airway and ProSeal Laryngeal Mask Airway in pediatric patients - Bikramjit Das; Shahin N Jamil; Subhro Mitra; Rohit K Varshney (Wolters Kluwer Medknow Publications, 2012)
Context: ProSeal Laryngeal Mask Airway (PLMA) is extensively being used in pediatric anesthesia. Aims: To evaluate the efficacy of PLMA as compared to Classic Laryngeal Mask Airway (CLMA) for airway maintenance in pediatric patients. Settings and Design: A prospective, randomized, Single-blinded study was conducted in a tertiary care teaching hospital. Materials and Methods: Sixty ASA I and II children were included. Patients were randomized to either size 2 PLMA or size 2 CLMA groups. Parameters noted were time for insertion, number of attempts, airway sealing pressure, blood pressures (systolic, diastolic, and mean), pulse rate, end-tidal carbon dioxide (EtCO 2 ), peripheral oxygen saturation (SpO 2 ), and postoperative change in abdominal circumference, and airway trauma. Statistical analysis used: Parametric data were analyzed with the unpaired t-test and non-parametric data were analyzed with the chi-square (c2 ) test. Unless otherwise stated, data are presented as mean (SD). Significance was taken as P < 0.05. Results: There was no statistical difference between the two groups for the success rates at the first attempt of insertion, airway sealing pressure, hemodynamic responses, SpO 2, EtCO 2 and postoperative changes in abdominal circumference. Patients in the PLMA group had longer time of insertion and higher incidence of airway trauma. Conclusions: The PLMA and the CLMA were comparable for hemodynamic and ventilatory parameters and change in abdominal circumference; however, the time taken for insertion and airway trauma was more with PLMA.